2022
DOI: 10.1038/s41467-021-27912-2
|View full text |Cite
|
Sign up to set email alerts
|

Observation and rationalization of nitrogen oxidation enabled only by coupled plasma and catalyst

Abstract: Heterogeneous catalysts coupled with non-thermal plasmas (NTP) are known to achieve reaction yields that exceed the contributions of the individual components. Rationalization of the enhancing potential of catalysts, however, remains challenging because the background contributions from NTP or catalysts are often non-negligible. Here, we first demonstrate platinum (Pt)-catalyzed nitrogen (N2) oxidation in a radio frequency plasma afterglow at conditions at which neither catalyst nor plasma alone produces signi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 54 publications
3
83
0
Order By: Relevance
“…The measurements reported here suggest that this mechanism alone cannot account for the ammonia produced in the reactor. Other activation pathways, such as nitrogen-vibrational excitation and enhanced dissociative adsorption, , must also play a role. We also point out that the nitrogen fixation efficiency increases with the amount of hydrogen introduced into the plasma volume.…”
Section: Resultsmentioning
confidence: 99%
“…The measurements reported here suggest that this mechanism alone cannot account for the ammonia produced in the reactor. Other activation pathways, such as nitrogen-vibrational excitation and enhanced dissociative adsorption, , must also play a role. We also point out that the nitrogen fixation efficiency increases with the amount of hydrogen introduced into the plasma volume.…”
Section: Resultsmentioning
confidence: 99%
“…The reports available to date describe a combination of plasma with heterogeneous catalysts (both downstream and inside the active plasma compartment), which achieve a plasma-catalysis synergy, reducing the energy consumption of nitrogen fixation. [25,35,36] While the exact nature of such synergy remains an open question and likely depends on each specific case (e. g., plasma parameters), we can hypothesize the possibility of coupling our plasma process with catalysis to further decrease the EC of our plasma-based nitrogen oxidation process.…”
Section: Plasma Process For the Conversion Of Air To No Xmentioning
confidence: 99%
“…This simplification has negligible influence on microkinetic rates versus models parametrized with a harmonic oscillator model . The nonsteady state surface coverages in temperature-programmed reactions were solved with a mean-field microkinetic model . The coverage of surface species i is written as an ordinary differential equation (ODE) θ i t = θ i true( T β true) = j c i j r j and r j = k + j i θ i c i j i P i c i j k j i θ i c i j i P i c i j where β (15 K min –1 ) is the temperature ramping rate, r j is the net rate of reaction j , and c ij is the stoichiometric coefficient of i in reaction j .…”
Section: Experimental Sectionmentioning
confidence: 99%
“…11,12 Recent research has shown that nonthermal plasma activation of N 2 enables nitrogen adsorption on metal surfaces under conditions at which the materials are not thermally active for N 2 dissociation. 13−18 These nitrogen intermediates provide access to cyanide, 19,20 nitric oxide, 21 and ammonia 18 at mild conditions. Further, experiments indicate that optimal catalysts for plasma-promoted NH 3 synthesis are different from optimal thermal catalysts.…”
Section: ■ Introductionmentioning
confidence: 99%